Digital Tools for Co-working Space Batununggal Using Digital-Ads, AR-Based Socmed Content, and Enterprise Resource Planning - Bethani Suryawardani; Astri Wulandari; Gandeva Bayu Satrya; Dandy Marcelino; Mochamad Yudha Febrianta; Tarandhika Tantra; Fat’hah Noor Prawita (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluhan Pembangunan Indonesia), 2023)
The rise of information and technology requires all businesses and nonprofits to digitize. The co-working facility in Bandung's Batununggal District does the same. Batununggal co-working facility intends to promote locals' creativity and host start-up actors. This community service targets MSME actors and inhabitants in Bandung's Batununggal subdistrict, those who have established a business and those who will establish a business. Workshops on digital technologies, digital ads, and AR-based social media content offer business actors insight and competence. Participants also received training on enterprise resource planning to help manage and integrate corporate operations in Batununggal, Bandung. This series of community service activities increased participants' insight into digital-based promotional strategies and the use of digital tools and digital ads for their products; increased participants' insight and competence in managing and integrating business using the ERP system; trained participants to use AR technology on social media, especially Instagram, to promote their products.